Peripheral endocannabinoids regulate skeletal muscle development and maintenance - Dongjiao Zhao; Amber Pond; Bruce Watkins; Dave Gerrard; Yefei Wen; Shihuan Kuang; Kevin Hannon (PAGEPress Publications, 2010)
As a principal tissue responsible for insulin-mediated glucose uptake, skeletal muscle is important for whole-body health. The role of peripheral endocannabinoids as regulators of skeletal muscle metabolism has recently gained a lot of interest, as endocannabinoid system disorders could cause peripheral insulin resistance. We investigated the role of the peripheral endocannabinoid system in skeletal muscle development and maintenance. Cultures of C2C12 cells, primary satellite cells and mouse skeletal muscle single fibers were used as model systems for our studies. We found an increase in cannabinoid receptor type 1 (CB1) mRNA and endocannabinoid synthetic enzyme mRNA skeletal muscle cells during differentiation. We also found that activation of CB1 inhibited myoblast differentiation, expanded the number of satellite cells, and stimulated the fast-muscle oxidative phenotype. Our findings contribute to understanding of the role of the endocannabinoid system in skeletal muscle metabolism and muscle oxygen consumption, and also help to explain the effects of the peripheral endocannabinoid system on whole-body energy balance.